Biologic Drugs for the Treatment of Noninfectious Uveitis. Issue 1 (January 2021) - Ferreira, Lisia Barros; Smith, Anthony J.; Smith, Justine R.
Abstract : Abstract: The management of noninfectious uveitis is constantly evolving. A new "biologic era" in treatment began after the effectiveness of tumor necrosis factor-alpha blocking drugs was demonstrated in rheumatologic inflammatory diseases. The goal of specific immunomodulation with a biologic drug is to target inflammation at the molecular level with a low rate of serious adverse events. The purpose of this review is to summarize current knowledge of biologic drugs in the treatment of noninfectious uveitis by describing clinical studies and recent pharmacological developments.